Oblicz:
a)(-13)*(-2)*1/2*(-5)=
b)(-14)*(-0,7)*(-1 3/7)=
c)(-1/3)*1 1/5*(-12)*(-1/6)=
d)(-3 2/3)*0,3*(-10)*(-6/11)=
e)(-6/7)*(-4,2)*(-1)*0=
f)(-100)*3,125*(-1 1/7)*(-1/25)=
2.Uprość wyrażenia i oblicz.
a)(-3/5)*(-20/27)*15*(-40)*(-9/16)*0,15=
b)-1 2/3*(-0,6)*1,4*(-4/21)*(-1,5)*(-3,1)=
c)-20 5/8*(-4/11)*(-7,5)*0,16*(-1/27)*3 1/3=
d)12 4/5*(-0,003)*(-1 7/8)*(-4 4/9)*(-3 1/8)*0,024=
e)2 1/5*3*(-2)*(-2,5)*(-2/3)*0,3=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T18:09:35+01:00
A)(-13)*(-2)*1/2*(-5)= 26 *1/2 *(-5)=13*(-5)=-65
b)(-14)*(-0,7)*(-1 3/7)=(-14)*(-7/10)*(-10/7)=(-14)*(-1)=14
c)(-1/3)*1 1/5*(-12)*(-1/6)=(-1/3)*6/5*(-12/1)*(-1/6)=(-2/5)*2=-4/5
d)(-3 2/3)*0,3*(-10)*(-6/11)=(-11/3)*3/10*(-10/1)*(-6/11)=
(-11/10)*(-10/1)*(-6/11)=11/1* (-6/11)=-6
e)(-6/7)*(-4,2)*(-1)*0=0
f)(-100)*3,125*(-1 1/7)*(-1/25)=(-100/1)*3 125/1000 *(-8/7)*(-14/10)=(-100/1)*3125/1000*8/5= -312,5 *8/5= -3125/10*8/5=
-2500/5=-500
1 5 1